The Effect of Storage and Time of Blood Specimen Examination of Plasma Prothrombin Time and Activated Partial Thromboplastin Time Stabilities (Indian Journal of Forensic Medicine & Toxicology, 2020)
his was an analytical study with cross sectional design. Collection of blood specimens was carried out byconsecutive sampling during March-June 2019. Blood specimens in this study were healthy adults aged ?21years who underwent general medical check-up or blood donors who met the inclusion criteria and signedinformed consent. A total of 71 samples were stored at room temperature and temperature 4-8 °C, then PT(prothrombin time) and aPTT (activated partial thromboplastin time) checks were carried out at 0, 4, 12, and24 hours. Data were analyzed by using Kolmogorov-Smirnov Test, paired t test and Wilcoxon Signed RankTest. There were differences in the results of PT in the room temperature specimens and 4-8 °C at 4 hours,12 hours, and 24 hours with p value <0.001. This was also found in the aPTT parameter, but for specimensat 4-8 °C at the 24th hour examination the results of changes in aPTT were not statistically significantwith p values 0.062. Different PT and aPTT tests at the two storage areas and at different examinationtimes obtained different and statistically significant results with p value <0.001. Examination of hemostasisphysiology requires special attention, where pre-analytic plays an important role which can influence theoverall test results. The aspects of time and storage on the stability of PT and aPTT specimens are illustratedin this study where significant differences were obtained with p values <0.001. Examination and storage ofcoagulation study specimens in accordance with CLSI recommendations will provide accurate results andaccurately describe the state of the specimen according to the patient’s clinical condition.